2018
DOI: 10.15611/fins.2018.1.04
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Nexus Between Financial Deepening and Economic Growth: Evidence From Ukraine

Abstract: In this paper systemic problems of Ukrainian banking sector are reviewed and the solutions are offered. The main objective of the study is to examine the relationship between a financial deepening and economic growth in Ukraine by estimating several multiple regression models over the 1993 to 2015 period. A real GDP growth per capita was used as an indicator for the economic growth. The domestic credit to private sector (% of GDP) was used as an index of financial depth. The study concludes that financial deep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 10 publications
(7 reference statements)
0
4
2
Order By: Relevance
“…Due to rather small number of observations per variable (12), a number of conclusions cannot be reliably made: namely, on the normality of residuals distribution (and thus whether the sample is an outlier or not). It is worth mentioning that modification of financial depth indicators makes the model results not directly comparable to previous similar study (e.g., Kondrat and Kots [80]). The descriptive statistics are presented in Table 7 The independent variables of this model describe 99.7 % of variation of the dependent variable, which denotes its relatively high quality.…”
Section: Estimation Of Financial Depth-economic Growth Nexuscontrasting
confidence: 63%
See 1 more Smart Citation
“…Due to rather small number of observations per variable (12), a number of conclusions cannot be reliably made: namely, on the normality of residuals distribution (and thus whether the sample is an outlier or not). It is worth mentioning that modification of financial depth indicators makes the model results not directly comparable to previous similar study (e.g., Kondrat and Kots [80]). The descriptive statistics are presented in Table 7 The independent variables of this model describe 99.7 % of variation of the dependent variable, which denotes its relatively high quality.…”
Section: Estimation Of Financial Depth-economic Growth Nexuscontrasting
confidence: 63%
“…The studies devoted to the dependence of financial depth on economic development mainly focus on the technical aspects of the calculation itself and come to the expected result, i.e., the relationship exists and is significant. For instance, Kondrat and Kots [80], using linear regression of the dependence of GDP per capita on loans to the private sector to GDP for 1993-2015, conclude that there is a positive correlation between these indicators, and, therefore, that there is a positive relationship between financial depth and economic development in Ukraine. Bogdan and Lomakovych [81] draw attention to the relatively low level of financial depth in Ukraine, which contributes to the increase in the riskiness of lending, complicates the servicing of already existing debt and contributes to the increase of macroeconomic instability.…”
Section: Outlines Of Financial Depth-economic Growth Nexus Theorymentioning
confidence: 99%
“…The study of the financial depth-economic growth nexus in Ukraine, conducted by Kondrat and Kots (2018) is based on a longer time period (22 years) than this study (12 years), and uses the standard domestic credit to GDP ratio taken from the World Bank database, thus being more directly comparable to Russeau and Wachtel's (2005) results. However, the relationship between financial depth and GDP growth in Ukraine, discovered by Kondrat and Kots (2018), is both positive and linear. This diverges from the findings of this study, since the model, described in the previous section, gives out a linear and negative relation.…”
Section: Discussionmentioning
confidence: 98%
“…Bublyk (2018) uses a wide set of banking-sector-focused indices, mostly adherent to financial depth index calculation variants, to investigate the transformation of the Ukrainian financial sector during 2003−2017. Kondrat and Kots (2018) use regression analysis to study the interrelation between economic growth, which they define as GDP per capita, and financial depth, which they define using the domestic credit to GDP ratio, in order to assess the impact of financial depth on economic growth in 1993−2015. The authors found a clear positive linear relationship between financial depth and economic growth in Ukraine.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation